(untitled) (The Journal of Academic Development, 2025)
The main purpose of this study is to examine the effect various bank specific factors on the market price per share of Nepalese commercial banks. Descriptive and causal comparative research design was carried out to complete this study. The sample comprises 10 commercial banks listed in NEPSE with 100 bank-years observation for the period of 2013/14 to 2013/24. Descriptive statistics, correlation analysis and regression analysis were performed to conduct this study. The results indicated that there were significant positive relationships between market price per share and earnings per share, price earnings ratio, return on equity, cash dividend and stock dividend, while there is a positive relationship with dividend pay-out ratio but statistically insignificant. Additionally, the regression result revealed that price to earnings ratio had the strongest positive impact on market price per share, followed by stock dividend, earnings per share, DPR and ROE whereas cash dividend has negative impact on the MPS of commercial banks in Nepal but statistically insignificant. Based on these findings, it can be concluded that Nepalese commercial banks can enhance their market price per share by focusing on improving their earnings per share, price earnings ratio, and stock dividend. Further, this study helps to provide useful insights regarding dividend practices in Nepalese commercial banks to regulators, policymakers, bank managers, and investors.